China’s bilateral diplomacy in the Arctic - Peng, Jingchao; Wegge, Njord (Polar Geography, 2015)
This is an Accepted Manuscript of an article published by Taylor & Francis in Polar Geography on 11 December 2015, available online: http://www.tandfonline.com/10.1080/1088937X.2015.1086445 . This article investigates China's bilateral diplomacy in the Arctic towards the USA, Canada, Denmark/Greenland, Norway, Russia, and Iceland. In seeking to identify (1) the most important bilateral issues, (2) whether China's diplomacy towards some of Arctic states has been more successful than others, and (3) the long-term goals of China's Arctic diplomacy and presence, the article utilizes insights from theories of diplomacy in IR as well as the particular historical experiences of the PRC. It concludes with identifying how Beijing's utmost concern when it comes to foreign policy still centers on promoting economic benefits and creating a global presence conducive to economic growth. Yet, while economic factors undoubtedly preoccupy Chinese decision-making in the Arctic, Chinese representatives currently speak less about economic development than about their environmental concerns. Chinese footprints in the Arctic have been adequately established primarily in the scientific research field, while commerce and multi-lateral governance are secondary. Further, it is also apparent that China has been developing contracts with the smaller Arctic powers of Denmark and Iceland (and earlier also attempted to do so with Norway) to facilitate collaborations in both Arctic research as well as economic development. With the bigger Arctic powers, such as the USA and Russia, China appears to prioritize other, more pressing bilateral issues than those pertaining solely to the Arctic.